Laser-induced graphene from commercial polyimide coated optical fibers for sensor development - Martins, Luís; Kulyk, Bohdan; Theodosiou, Antreas; Ioannou, Andreas; Moreirinha, Catarina; Kalli, Kyriacos; Santos, Nuno; Costa, Florinda; Pereira, Sónia O.; Marques, Carlos (My University, 2023)
Direct laser scribing (DLS) technology is applied to commercial polyimide (PI) coated optical fibers producing laser-induced graphene (LIG) coated optical fibers. The PI-coated optical fiber is first inscribed with off-center Bragg gratings via point-by-point method using a femtosecond laser system. Then, the off-center Bragg grating is irradiated with a CO2 laser and the PI coating is photothermally converted into LIG without affecting the grating. Scanning electron microscopy (SEM) and Raman spectroscopy prove the presence of the laser-induced graphene layer on the optical fiber, and Fourier transform infrared (FTIR) spectroscopy confirms that all the PI coating was converted into LIG. The resulting LIG-coated off-center Bragg grating (FBG) sensors respond to variations of the surrounding refractive index (RI) with a sensitivity of 38.08 ± 1.57 nm per RI units (RIU). In addition, after removal of the PI coating, obtaining a bare-FBG, the sensitivity decreases to 25.63 ± 0.66 nm RIU−1. Therefore, this strategy, here reported for the first time, paves the way to produce promising novel optical transducers aiming to develop bio- and chem-sensing devices.
Keywords: Commercial polyimide fiber; Laser induced graphene; Process graphene on fiber; Sensors